Conformational control of photoinduced charge separation within phenothiazine-pyrene dyads - Kurzawa, Jana; Acar, Nursel; Schneider, Siegfried; Daub, Jörg; Clark, Timothy; et al. (Journal of Physical Chemistry A, 2002)
Electron donor-acceptor systems, in which phenothiazine is tethered to pyrene by means of a phenyl bridge, exhibit a dual emission in moderately and very polar solvents. Employing steady-state and time-resolved fluorescence spectroscopy, we were able to provide evidence that the "blue" and "red" emission bands originate from different conformers. The ground-state geometry of the majority species is identical to that found in the crystalline state (the quasi-equatorial conformer). This conformation executes a fast electron-transfer process accompanied by significant structural relaxation. Consequently, its fluorescence exhibits a large solvatochromic shift typical for charge-transfer states. The photophysical properties of the minority species (the quasi-axial conformer) vary significantly with the substitution pattern of the bridging phenyl ring. In part, this difference is related to the orientational factor, K, governing the rate of energy transfer between the pyrene and phenothiazine moieties. In the para-substituted derivative, fluorescence emission from both the excited phenylpyrene and the phenylphenothiazine subsystem can be observed. In the meta-substituted derivative, fluorescence originates mainly from the primarily absorbing phenylpyrene subsystem. In nonpolar solvent (cyclohexane), the nature of the fluorescing state differs for the para- and meta-substituted compounds. Whereas in the former, the fluorescence originates from the locally excited phenothiazine, it is governed by emission from a structurally modified CT state in the latter derivative. Semiempirical (AM1/CI) molecular orbital calculations with a continuum solvent treatment have been used to investigate the different states involved and provide explanations for the observed results. The calculations reveal the existence of an intermediately populated CT state in which the negative charge is partly localized in the bridge as well as in the pyrene acceptor.